Determinant attributes valued by Brazilian retail construction materials consumers - Pizzinatto, Nadia Kassouf; Cunha, Christiano França da; Sarquis, Alessio Bessa; Pizzinatto, Andrea Kassouf; Lopes, Evandro Luiz (Revista de Administração da UFSM, 2020)
This article analyzes the determinant attributes valued by the retail consumer of construction materials in São Paulo State, Brazil, using a survey with 450 consumers from two large retail networks of construction materials in three Brazilian cities testing two hypotheses regarding the differences in attributes valued by the consumes when choosing a point of sale. The Correspondence Analysis (CA) was used to examine relationships of the valued attributes from one city to another. The results showed that there are 45 determinant attributes valued by the consumer, classified into 9 categories (relationship, service, convenience, pricing policy, point of sale, product, services, promotion and brand). The categorization proved to that some categories, for example, convenience, have different meanings in cities with different profiles. Other attributes appreciated by customers were product variety, location of store, personalized service, price, quality of products, and store image. The results of the study contribute to the field by enhancing knowledge of determinant attributes valued in construction materials retail, helping store managers to shape their marketing strategies.